Flowering curves and the summer-gap mystery - Harper, Geoffrey; Rogers, Elizabeth (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2011)
Results from year-round weekly monitoring of 93 taxa (179 accessions) at the Royal Botanic Garden Edinburgh (RBGE) are presented in the form of flowering curves. These are provisionally grouped into classes, and hypotheses are suggested to explain the different patterns. Attention is drawn to a prominent ‘summer gap’ in flowering in some species, and possible explanations for the gap are discussed.